The Cost Efficiency of UK Debt Management: A Recursive Modelling Approach - M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper presents an empirical analysis of the efficiency of the UK debt management authorities's (DMA) behaviour from a cost minimisation perspective over the period January 1985 to March 1995. During this period, the maturity structure of the government's bond portfolio was subject to frequent finetuning, aimed principally at lowering interest costs. We examine the efficiency of the DMA's behaviour from a cost minimisation perspective. Using a bi-variate version of the recursive modelling procedure applied to forecasting stock returns by Pesaran and Timmermann (1995, 2000), we show that bond returns are forecastable but the predictive power of macroeconomic variables is time dependent. We simulate the impact of adjusting the bond portfolio in response to our forecasts. The simulated average interest costs are lower than those resulting from the DMA's actual real-time behaviour. However, a substantial reduction in interest costs requires large monthly changes in the portfolio's maturity structure.
Keywords: 330; Government debt management; cost minimisation; recursive modelling